The Effect of Learning Media on Increasing Learning Motivation in terms of Creativity for Class X students in State Aliyah Madrasah in Kudus Regency - Wasino, Wasino; Hadromi, Hadromi; Wardana, Shony (Universitas Negeri Semarang, 2025)
This research aims to find out: The difference of significant effect between the use of multimedia and worksheet media, high and low creativity levels on the students learning motivation. and the significant interaction effect between the use of learning media and the students' creativity level on the students learning motivation in MAN Kudus Regency. The research method employed was experimental method. The population of research were all grades X of MAN 1 and MAN 2 in Kudus Regency. The sample of research consisted of 1 class grade X of MAN 2 and 1 class of grade X of MAN 1 as the control group. The sampling was done using